2022
DOI: 10.1021/jacs.2c09263
|View full text |Cite
|
Sign up to set email alerts
|

How Do Preorganized Electric Fields Function in Catalytic Cycles? The Case of the Enzyme Tyrosine Hydroxylase

Abstract: Nature has devised intrinsic electric fields (IEFs) that are engaged in electrostatic catalysis of enzymes. But, how does the IEF target its function in enzymes that involve several reaction steps in catalytic cycles? To decipher the impact of the IEF on the catalytic cycle of an enzyme system, we have performed molecular dynamics and quantum-mechanical/molecular-mechanical (QM/MM) simulations on tyrosine hydroxylase (TyrH). The catalytic cycle of TyrH involves two reaction stages: the activation of H2O2 to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 117 publications
1
50
0
Order By: Relevance
“…The IEF was computed as described in previous studies. , Briefly, it is calculated with Coulomb’s law, whereby the atoms are treated as point charges and their positions are determined by the QM/MM-optimized structures. The magnitude of the point charge was obtained from the AMBER ff14SB force field and TIP3P model for the protein residues and water molecules, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The IEF was computed as described in previous studies. , Briefly, it is calculated with Coulomb’s law, whereby the atoms are treated as point charges and their positions are determined by the QM/MM-optimized structures. The magnitude of the point charge was obtained from the AMBER ff14SB force field and TIP3P model for the protein residues and water molecules, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To gain some clues on this, we have analyzed the intrinsic electric field (IEF) along the Fe–O bond from the MD trajectory of LiP-Cpd I at pH = 7 vs pH ∼ 3. Existing studies have shown that the IEF along the Fe–O bond has significant effects on the reactivity and redox potential of the Heme-Cpd I species . For pH = 7, the calculated average IEF value is −72 MV/cm (Figure S28).…”
Section: Resultsmentioning
confidence: 91%
“…Existing studies have shown that the IEF along the Fe–O bond has significant effects on the reactivity and redox potential of the Heme-Cpd I species. 89 For pH = 7, the calculated average IEF value is −72 MV/cm ( Figure S28 ). Such a negative value suggests that the redox potential of Cpd I is intrinsically inhibited by the protein environment of LiP.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the TyrH scaffold and the QM region in the reactant state (RS) and TS of the O–O heterolysis reaction were obtained from our previous QM/MM study . The QM region contains the heme with the Fe-OOH moiety, the ligand imidazole ring, and the substrate (see Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical studies also provide significant insights into the catalytic effects of electric fields in enzymes. For instance, Warshel et al employed the empirical valence bond (EVB) method to quantify the catalytic effect of the preorganized electrostatic environment in various enzymes. ,, Alexandrova’s group have shown that the effect of electrostatic preorganization can be reflected by the change of geometry of charge density in the theoretical framework of Quantum Theory of Atoms in Molecules (QTAIM). Head-Gordon’s group evaluated the transition-state free energy stabilization based on the interaction energy of residue electric fields with bond dipoles in the reactant and TSs, which successfully guide the optimization of the electric field for improving the catalytic efficiency of a designed Kemp eliminase through mutation in the protein scaffold residues. ,, The application of oriented external electric fields (OEEFs) in computational models has also been used to infer how the electric fields affect the energetics of chemical reactions. ,, …”
Section: Introductionmentioning
confidence: 99%